Hipervolemia Pada Pasien Congestive Heart Failure (CHF) - Yeni Eka Astuti; Yuyun Setyorini; Akhmad Rifai (Poltekkes Kemenkes Surakarta, 2018)
Background: Congestive Heart Failure (CHF) is a condition in which the heart is unable to pump blood normally, causing disturbed venous return pressure to cause edema. The problem that arises is hypervolemia or intracellular fluid resuscitation to the interstitial that causes edema so that can be arranged nursing intervention one of them is giving diuretic and monitor fluid balance. Describes nursing care performed in Congestive Heart Failure (CHF) patients with hypervolemia. Method: This study uses data analysis method that is conducting the nursing process of two patients Congestive Heart Failure (CHF) who suffered from Hypervolemia disorder and then compared with case study journal as well as other sources. Result: After nursing action in both patients the Hipervolemia problem is equally partially resolved by fluid restriction nursing interventions, and the administration of diuretics. Conclusion: In providing nursing care to patients with Congestive Heart Failure (CHF) should pay attention to fluid restriction and appropriate diuretic administration to reduce edema.